Cutaneous Lesions in Freshwater Turtles (Emydura macquarii krefftii and Myuchelys latisternum) in a Rainforest Creek in North Queensland, Australia - Wirth, Wytamma; Elliott, Elizabeth; Rudd, Donna; Hayes, Linda; Maclaine, Alicia; Mashkour, Narges; Ahasan, Shamim; Gorm Dahl, Jakob; Drane, Kezia; Ariel, Ellen (Frontiers in Veterinary Science, 2020)
Freshwater turtles inhabit most rivers and creeks on the east coast of Australia, but some species are only found in specific catchments, which makes them vulnerable to extinction. During annual fieldtrips to Alligator Creek, North Queensland, the resident population of Myuchelys latisternum and Emydura macquarii krefftii in a natural pond, just outside Bowling Green national park, have been surveyed for a number of years and demographic data recorded against tagged turtles. Rounded, cutaneous lesions on individual animals were first noted in August 2016. Turtles living in the upstream sections of the creek were not affected. An initial investigation into the cause of the lesions ruled out pollutants and although the bacterial communities appeared to be different on turtles with lesions, a causative agent was not identified. Attempts to isolate virus in culture was not successful and specific PCRs for ranavirus, papillomavirus, adenovirus and herpesvirus did not identify their presence, but histological examination revealed intra-nuclear inclusions. Blood biochemical parameters, body condition and activity levels were not significantly different between affected turtles and those without lesions. The turtles in this pond were monitored regularly over the following three years with 249 M.latisternum and 192 E.m.krefftii captured, tagged and released. The prevalence of the lesions fluctuated with season from 0 to 77 and 68% respectively, but did not vary significantly between species or sex in adults. There was a tendency for larger animals to be more likely to have lesions. The position of the lesions on the turtles was mostly on dorsal surfaces, distally on the legs and proximal on the tales of males, indicating that the initial lesion may have been associated with a behaviorally induced trauma. Recaptured animals (n=43) during this period, provided records of lesion progression over time and while some healed up between capture events, others persisted for up to 24 months. Some turtles were repeatedly captured without lesions. Intra-species aggression associated with seasonal behaviors could potentially be the primary cause of skin trauma, followed by a secondary invasion of an unusual pathogen present in the environment.